Can we get a job? employability skills acquisition during educational experience of student with disability - Omar, Muhd Khaizer; Che Mat, Hanizan; Mohd Puad, Mohd Hazwan; Yaakub, Mohamad (Academia Industry Networks, 2022)
The issues regarding employability have been a major concern and employability for Person With Disability (PWD) is more alarming. Sustainable Development Goal (SDG) noted that PWD is viewed as weak, dependent, and incompetent. They are also categorized among the poor, less educated and poor health. This study employs a qualitative method by using a case study approach through interviews. Researchers have prepared semi-structured interview protocols and the interviews were conducted to obtain more in-depth input. The session was recorded and feedback was analyzed by using thematic analysis. The research participants involved a group of students at skill training institutions under the Malaysian Association for the Blind (MAB) and participants with Attention-Deficit/ Hyperactivity Disorder (ADHD) syndrome who are currently pursuing study at Universiti Putra Malaysia (UPM). The findings from the interview clustered to five themes (i) communications, (ii) writing, (iii) digital, and (iv) critical thinking and analytical skills as well as (v) practical skills. Researchers have taken into consideration ethical issues such as confidentiality of the data and anonymity of participants. All respondents are given nicknames and they also clearly understand that they are free to withdraw from this study at any time without giving any explanation. The development of employability skills is a pivotal factor to warrant workforce opportunities for PWD. The current job market often results in discrimination of PWD and marginalized PWD from enjoying equal chances in employment. The findings suggest remodelling and modification of educational training modules for PWD by embedding employability skills element germane to the current job landscape.